2012
DOI: 10.7439/ijbr.v3i6.484
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary complications in Rheumatoid Arthritis

Abstract: Rheumatoid Arthritis (RA) is a chronic systemic disease with decreased physical function. It is characterised by both articular and extra-articular manifestations. Pulmonary involvement is common and its complications are a leading cause of death in patients with RA. The present study was undertaken with the objective of analysing the incidence and severity of pleuro pulmonary complications in RA. A cross-sectional study on 36 patients with RA was carried out along with a detailed history, general and systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(14 reference statements)
0
0
1
Order By: Relevance
“…Mean disease duration was 8.1 years. 10 But in our study most patients having pulmonary involvement having duration of illness between 0 to 3 years (66%), followed by 34% between the age more than 3years.This difference is because of lesser number of sample size included in the study. Vergnenegre et al, reported a significant correlation between abnormal FEF 25-75% and duration of articular disease in non-smokers with RA.…”
Section: Exclusion Criteriacontrasting
confidence: 49%
“…Mean disease duration was 8.1 years. 10 But in our study most patients having pulmonary involvement having duration of illness between 0 to 3 years (66%), followed by 34% between the age more than 3years.This difference is because of lesser number of sample size included in the study. Vergnenegre et al, reported a significant correlation between abnormal FEF 25-75% and duration of articular disease in non-smokers with RA.…”
Section: Exclusion Criteriacontrasting
confidence: 49%